Electoral Violence and Arms Proliferation in Nigeria: Causes, Consequences and Way Forward - Ola, Adegboyega Adedolapo (African Journal of Stability and Development (AJSD), 2018)
One of the greatest challenges facing governance and political systems in Africa is the violence that ensues whenever elections are conducted. The main objective of the study was to examine the relationship between electoral violence and arms proliferation in Nigeria. It also examines the causes and implications of electoral violence on the electorate, entire community and Nigeria’s political system. The adopted research methodology is desktop research, where information was obtained from journals, textbooks, conference papers and others. The findings of the study revealed a link between small arms and electoral violence, and it was discovered that illicit proliferation of small arms is a major cause of electoral violence in Nigeria. The study established the lack of trust of the politicians on the electoral process which is a challenge to the nation’s nascent democracy and sustainability of peace and security. The study therefore, recommended that security agencies that are involved in the electoral system should be trained on electoral security system, in order to improve the level of security in the country. The study also posits that the control of small arms is very essential in curtailing the high level of illicit flow of arms in the country before and during elections.